The Effect Of Tax Avoidance And Corporate Governance On Company Value (Empire Study On Manufacturing Companies In The Consumer Goods Industry Sector Listed On The Indonesia Stock Exchange (Idx) 2015-2018 Period) - Mayangsari, Anisa; Cahyana, Agus; Mulyana Dali, Rahmat; A. Syukur, Dudung (Program Studi Akuntansi Universitas Ibn Khaldun Bogor, 2022)
This research is based on the fact that an investor who wants to invest in their shares sees the value of the company. This study aims to examine: 1) The effect of tax avoidance on firm value, 2) The effect ofl corporate governance on firm value. This type oflresearch is quantitative research. The population of this research is manufacturing companies in the consumer goods industry which are listed on the Indonesia Stock Exchange (BEI) for the 2015-2018 period. The sampling technique in this study was purposive sampling. The data of this study used financial report data and annual reports obtained by 34 companies with a research period of 4 years and 37 outlier data so that the total sample size was 99 research data. The type of data used is secondary data obtained from www.idx.co.id and www.sahamok.com. The analytical test used is multiple linear regression analysis with the statistical analysis test method using the SPSS version 26 software program. The results showed that: 1) Tax avoidance has a positive effect on firm value. 2) Corporate governance with indicators: The Board of Directors has a negative effect on firm value, the proportion of the Independent Commissioner has no negative effect on company value and the Audit Committee has a positive effect on firm value.